Age‐associated changes in hippocampal‐dependent cognition in Diversity Outbred mice. Issue 11 (11th June 2014) - Koh, Ming Teng; Spiegel, Amy M.; Gallagher, Michela
ABSTRACT Episodic memory impairment due to aging has been linked to hippocampal dysfunction. Evidence exists for alterations in specific circuits within the hippocampal system that are closely coupled to individual differences in the presence and severity of such memory loss. Here, we used the newly developed Diversity Outbred (DO) mouse that was designed to model the genetic diversity in human populations. Young and aged DO mice were tested in a hippocampal‐dependent water maze task. Young mice showed higher proficiency and more robust memory compared to the overall performance of aged mice. A substantial number of the older mice, however, performed on par with the normative performance of the younger mice. Stereological quantification of somatostatin‐immunoreactive neurons in the dentate hilus showed that high‐performing young and unimpaired aged mice had similar numbers of somatostatin‐positive interneurons, while aged mice that were impaired in the spatial task had significantly fewer such neurons. These data in the DO model tie loss of hilar inhibitory network integrity to age‐related memory impairment, paralleling data in other rodent models. © 2014 Wiley Periodicals, Inc.